Preparation of Two-Layer Anion-Exchange Poly(ethersulfone) Based Membrane: Effect of Surface Modification - Lucie Zarybnicka; Eliska Stranska; Jana Machotova; Gabriela Lencova (International Journal of Polymer Science)
The present work deals with the surface modification of a commercial microfiltration poly(ethersulfone) membrane by graft polymerization technique. Poly(styrene-co-divinylbenzene-co-4-vinylbenzylchloride) surface layer was covalently attached onto the poly(ethersulfone) support layer to improve the membrane electrochemical properties. Followed by amination, a two-layer anion-exchange membrane was prepared. The effect of surface layer treatment using the extraction in various solvents on membrane morphological and electrochemical characteristics was studied. The membranes were tested from the point of view of water content, ion-exchange capacity, specific resistance, permselectivity, FT-IR spectroscopy, and SEM analysis. It was found that the two-layer anion-exchange membranes after the extraction using tetrahydrofuran or toluene exhibited smooth and porous surface layer, which resulted in improved ion-exchange capacity, electrical resistance, and permselectivity of the membranes.